Virus-like nanoparticle as a co-delivery system to enhance efficacy of CRISPR/Cas9-based cancer immunotherapy. (November 2020) - Liu, Qi; Wang, Chun; Zheng, Yadan; Zhao, Yu; Wang, Ying; Hao, Jialei; Zhao, Xinzhi; Yi, Kaikai; Shi, Linqi; Kang, Chunsheng; Liu, Yang
Abstract: The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-associated protein 9 (Cas9) system holds great promise for the cancer gene therapy. However, due to complicated signal networks and various compensatory mechanisms in tumors, adjusting a single molecular pathway has limited effects on cancer treatments. Herein, a virus-like nanoparticle (VLN) was reported as a versatile nanoplatform to co-deliver CRISPR/Cas9 system and small molecule drugs for effective malignant cancer treatment. VLN has a core-shell structure, in which small molecule drugs and CRISPR/Cas9 system are loaded in the mesoporous silica nanoparticle (MSN)-based core, which is further encapsulated with a lipid shell. This structure allows VLN maintaining stable during blood circulation. As reaching tumors, VLN releases the CRISPR/Cas9 system and small molecule drugs in response to the reductive microenvironment, resulting in the synergistic regulation of multiple cancer-associated pathways. By loading a single guide RNA (sgRNA) targeting programmed death-ligand 1 and axitinib, VLN achieved to disrupt multiple immunosuppressive pathways and suppress the growth of melanoma in vivo . More importantly, VLN can co-deliver almost any combination of sgRNAs and small molecule drugs to tumors, suggesting the great potential of VLN as a general platform for the development of advanced combination therapies against malignant tumors. Graphical abstract: Image 1 Highlights: A virus-like nanoparticle co-delivers CRISPR/Cas9 and small-molecule drug to tumor. The combined use of CRISPR/Cas9 and small-molecule drug can effectively treat cancer. This strategy can co-deliver any combination of CRISPR/Cas9 and small-molecule drug. The universal platform enables the development of new cancer combination therapies.